Heteroleptic neutral Ru(II) complexes based photodiodes - Elgazzar, Elsayed; Dayan, O.; Serbetci, Z.; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2017)
The two complexes Ru(II) containing 2,6-bis(benzimidazol-2-yl) pyridine and 2-pyridine and 2-quinoline carboxylates were synthesized to fabricate organic photodiodes. The electrical properties of Au/Ru(II) complex (I)/n - Si/Al and Au/Ru(II) complex (II)/n - Si/Al diodes were investigated by current-voltage and capacitance-voltage measurements. The fabricated devices give a high rectification behavior with rectification ratio of 2.4 x10(4) - 2.1 x10(3) at +/- 4 V. The diodes exhibited a high photoconductivity based on trap levels within band gap. The series resistance and barrier height were calculated from (C - V) measurements and compared to other of (I - V). The obtained results indicate that the prepared photodiodes can be used as photosensor for optoelectronic applications.
Keywords: Ruthenium organic material; Organic photodiode